Review about chemical constituents and pharmacological of Morinda citrifolia L. (Rubiaceae) - Lý, Hồng Hương Hạ; Nguyễn, Thế Nhựt; Nguyễn, Thị Hồng Yến; Đỗ, Thị Hoài Thương; Dương, Thị Lệ; Lê, Minh Khoa (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Herbs from nature are being widely used in healing and in traditional medicine in Vietnam and in many other countries around the world. In which Nhau (Morinda citrifolia L. Rubiaceae family) is known as a familiar medicinal herb of Southeast Asia and Australia. In this paper, the research team considers the chemical composition in parts of M. citrifolia such as leaves, fruits, seeds, roots, bark with therapeutic effects such as antiinflammatory, antibacterial, antiviral, antifungal, antioxidant, anticancer, vascular protector, cardioprotective, skin and bone regeneration, hypoglycemic, neuroprotective. At the same time, learn the mechanisms of testing the action of compounds on the body to apply to find cures for diseases. Based on published data and scientific studies, Nhau is really a potential medicinal plant because of the variety of chemical components and biological activities that this medicinal herb brings. With the above research results, it will be the foundation and premise for further studies on isolating active of M. citrifolia in the future.